HYBRID GRIDS ANALYSIS WITH RENEWABLE ENERGY AND THERMAL ENERGY FOR STREET LIGHT -A CASE STUDY - Ranjan, Rajeev; Nagar, Mahesh kr; Choudary, M.Nithin; Paswan, M.K.; kumar, Manish (International Journal of Research -GRANTHAALAYAH, 2018)
This paper presents a techno-economic assessment for a unique Isolated Hybrid Power System (IHPS) design which could be used for remote areas isolated from the grid which also has the capability of being operated as a smart the hybrid energy system considering solar and wind energy sources for the purpose of street lighting. Solar-Wind Street light is an intelligent, small scale, and off grid LED lighting system. The modelling design and simulations were based on Simulations conducted using the Data collected and HOMER Energy Planning and Design software tools. Its components are solar panel, wind generator system (PVC blowers), Dynamo, LDRs, battery, LED light, charge controller. The energy stored in battery during day time due to solar panel, get extracted by LEDs during the night time (because LDRs get activated due to absence of sun light). Wind also charges the batteries due to wind which is used for glowing street light. The advantage of this idea is to avoid daily running cost and make the system purely off-grid. In this prototype, we have used 12V DC system to supply energy to the lights.